Pengaruh Iklan Scarlett Whitening di Aplikasi TikTok terhadap Brand Awareness Generasi Z - Kezia Stephanie Halim; Wulan Purnama Sari (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
The Scarlett Whitening beauty product is widely known by TikTok and Instagram users because of the ads that attract attention, but researchers are more focused on the TikTok application. The study was conducted with the aim of knowing the effect of Scarlett Whitening advertisements in the TikTok application on brand awareness of generation Z. This study used a quantitative approach using survey research methods. The research was conducted by distributing questionnaires pretest to 30 respondents after testing valid and reliable then proceeding totests posttest to 100 respondents who used the TikTok application and who were followers of the official TikTok account Scarlett Whitening. The theory used in this research is advertising and brand awareness. The data validity technique used is the classical regression assumption test, simple linear regression test, correlation analysis. The results of the correlation test with a value of 0.638, which indicates that the advertising and image variables have a strong correlation, so in this study the results obtained indicate that Scarlett Whitening ads in the TikTok application have an effect on brand awareness of generation Z.Penelitian dilakukan dengan tujuan untuk mengetahui pengaruh iklan Scarlett Whitening di aplikasi TikTok terhadap brand awareness generasi Z. Penelitian ini menggunakan pendekatan kuantitatif menggunakan metode penelitian survei. Penelitian dilakukan dengan cara menyebarkan kuesioner pretest kepada 30 responden setelah teruji valid dan reliabel kemudian dilanjutkan ke uji posttest kepada 100 responden yang menggunakan aplikasi TikTok dan yang merupakan pengikut akun TikTok resmi Scarlett Whitening. Teori yang digunakan pada penelitian ini adalah iklan dan brand awareness. Teknik keabsahan data yang digunakan adalah uji asumsi regresi klasik, uji regresi linier sederhana, analisis korelasi. Hasil uji korelasi dengan nilai 0,638 yang menandakan variabel iklan dan citra memiliki korelasi yang kuat, sehingga dalam penelitian ini hasil yang didapat menunjukkan bahwa iklan Scarlett Whitening di aplikasi TikTok berpengaruh terhadap brand awareness generasi Z.